The inner level : How More Equal Societies Reduce Stress, Restore Sanity and Improve Everyone's Wellbeing - Wilkinson, Richard, ....-; Pickett, Kate, ....- (Milton Keynes : Allen Lane, 2018)
Richard Wilkinson and Kate Pickett's The Spirit Level, now published in more than twenty languages, has been one of the most influential non-fiction books published in the last decade, showing conclusively how less equal societies fare worse than more equal ones across a whole range of social measures - health, education, levels of violence, life expectancy and child wellbeing - and initiating the enormous public attention now given to the impacts of inequality. Based on an equally impressive range of data and analysis, The Inner Level now shows the impact inequality has on individuals: how it affects us psychologically, makes social relations more stressful, undermines self-confidence and distorts natural differences in personal abilities. It demonstrates that societies based on fundamental equalities, sharing and reciprocity produce much higher levels of wellbeing than those based on excessive individualism, competitiveness and social aggression. Like its predecessor, The Inner Level will transform ideas of how we should organise the way we live together. Richard Wilkinson Kate Pickett